Problem Perlindungan Hukum Terhadap Hak Nafkah dan Waris Anak luar Nikah dan Ibunya Tinjauan Maqāṣid al-Sharī'ah dan Keadilan Gender - Aula Yazid, Nur; Huda, Afiful (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
This study analyzes the legal protection issues concerning the civil rights of “anak oleh-oleh” (children born from relationships deemed illegitimate under Islamic law) and their mothers, particularly in relation to maintenance and inheritance rights. Employing a maqāṣid al-sharī‘ah approach and a gender justice perspective, the study aims to examine the gap between classical Islamic legal norms and contemporary demands for substantive justice. The research adopts a normative juridical method with conceptual and comparative approaches. The findings indicate that rigid interpretations of the concept of nasab (lineage) in classical fiqh have generated structural discrimination against children born out of wedlock and their mothers. Through the reactualization of maqāṣid al-sharī‘ah, especially the principles of ḥifẓ al-nasl (protection of lineage) and ḥifẓ al-māl (protection of property), combined with the integration of a gender justice perspective, this study proposes a more progressive conceptual reformulation to ensure fair and dignified legal protection for both children and mothers, without compromising the fundamental principles of Sharī‘ah.